An evaluation of the usefulness of stroke index values in the swimming training of people with disabilities - Seidel, W.; Klarowicz, A.; Rejman, M.; Szczepan, S. (Polish Journal of Sport and Tourism, 2016)
Introduction. When evaluating the swimming technique of people with disabilities, a particularly important factor, besides physiological aspects, is the efficiency of the effort expended. This suggests that assessing and monitoring the effectiveness of swimming should be a regular part of training for swimmers with disabilities. Therefore, it seems important to distinguish how changes occur in the parameters that determine the effectiveness of swimming. This is especially true of anaerobic lactic exercise as the lactic acid concentration in the blood increases significantly. The aim of this study was to evaluate the usefulness of calculating velocity and the stroke index in the swimming training of people with disabilities, along with the progressive fatigue of a high-intensity interval training workout. Material and methods. The sample comprised 12 elite competitors with a disability. The experiment consisted in swimming sequential distances of 48 m, 50 m, 52 m, and 54 m at maximum intensity. Competitors performed four sets of four repetitions with a 75-second interval between repetitions and 15 minutes of active resting between sets. All sets were recorded using five digital cameras with a frequency of 50 frames per second. The recorded material was analysed with the use of motion analysis software, and the stroke index was calculated. Results. There was found to be no significant change in the average swimming velocity during each set and corresponding repetition, which means that the participants were able to tolerate the training intensity. Also, the stroke index did not change to a statistically significant degree in either of the subsequent sets or the subsequent repetitions (p < 0.05). Conclusions. We conclude that analysing the value of the swimming stroke index for people with disabilities can be a diagnostic method for assessing the effectiveness of high-intensity interval training.